ANALISIS WACANA SARA MILLS DALAM FILM KARTINI SUTRADARA HANUNG BRAMANTYO - Achmad Sholeh; Sakrim; Rozekki (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2021)
The discourse in the film is not an impartial means, but tends to present certain actors as subjects who explain all certain events in the text discourse, but it also influences the meaning when received by the special people who read it. Such a position becomes part of the text element, in the sense that those who have the opportunity to define the reality of certain events when described to the public. In this study the focus is on knowing the position of the subject-object and the position of the writer and reader in the discourse, especially in the Kartini film by using Sara Mills's theory analysis discourse model, so in achieving that goal the writer raises the question of how to position the subject-object and the position of the writer-reader regarding the discourse contained in the Kartini Film. The research approach uses qualitative using the reading method. The method used in gathering data is by reading and recording techniques. The data source and subject of this research are Kartini films. The results show how one party is portrayed in a certain way and marginalized, especially the Kartini film. The subject position tends to be carried out by Kartini, a woman who is considered to be against tradition and against Regency rules. While the writer positions Kartini as the party that notifies the incident, so the text that appears leads the reader to interpret the text from the point of view experienced by Kartini, the position of the reader cannot change the discourse written by the writer because the reader cannot provide an argument to the author when there is a discrepancy in the contents which discusses the film.